Bringing Islamic tradition back to management development : A new Islamic Dawah based framework to foster workplace ethics - Muhammad, Kashif; Ernest Cyril, de Run; Mohsin, Abdul Rehman; Hiram, Ting (Emerald Group Publishing Limited, 2015)
Purpose – The purpose of this study is to understand the practice of Dawah among Muslims by discovering its perceived motives and benefits that can be replicated to organizational settings. Furthermore, the motives and benefits of performing Islamic Dawah are tied together to establish a Dawah based framework to foster ethical decision making in organizations. Design/methodology/approach – This qualitative study is based on interviews conducted among 40 male Muslims from Pakistan. The sample consists of Muslim scholars having strong religious knowledge, younger people and old-age Muslims. The data collected through the interviews are transcribed and content-analysed by using multiple coding schemes. Findings – The Islamic Dawah-based framework is based on five elements, which are self-reform, transcendence, complacency, dutifulness and pridefulness. The findings reveal that Muslim scholars put much emphasis on sharing of Islamic faith and livelihood among the members of the community, while the common people, both from the younger and older generations, are more concerned with establishing their own understanding of the Islamic value system and self-improvement. Aside from the spiritual impact that Dawah has on them, the role of family members in stimulating the practice of Dawah is highlighted. Practical implications – The study has managerial relevance in a way that the highlighted themes represented by a framework can be replicated to an organizational setting to impart a culture of ethicality which is purely based on Islamic tradition. The roles of peers, CEO and self-correction are pivotal to establishment of an ethical workplace culture. Originality/value – This study extends marketing knowledge in general and internal marketing knowledge specifically by presenting a first-ever Islamic Dawah-based model to foster workplace ethics.